(untitled) (Journal of Hama University, 2024)
This research experiment was conducted in the broiler laboratory in the Department of Animal Production, Faculty of Agricultural Engineering, Tishreen University, Lattakia Governorate, Syria. During the period of 2023. The aim of this study was to investigate the effect of exposing the classical music on a fertile eggs of the Japanese quail (Coturnix japonica) during the incubation period (18) days on some hatching parameters. Total of (180) eggs were randomly distributed into tow treatment (90) eggs each treatment and were replicated three times with (30) eggs per replication, using the completely randomized design. The first treatment T1 was exposed to a classical music program for (12) hours, from seven am to seven pm, and the second treatment was the control T0 without music. The music was provided by player (MP3) and portable bluetooth speaker. The results showed that a statistically significant (P≤0.05) were observed among the tow treatment, the averages of the hatchability (%) for the music treatment T1 were (90) % and the control T0 (83.33) %, as for the hatching time (364, 371) hour respectively, and for the average body weights on the 1st day were (9.58, 8.79) g respectively. Using the music system (12) hours a day have positive role, it contributed to stimulating embryonic growth and increase the hatchability %, and synchronization of the hatching process for the entire batch. Also increased the average body weights of the chicks, improved the quality and performance of newly hatched chicks, as it reduced the chicks’ fear and stress factor, and improved the birds’ adaptation and acclimatization to the new environment after hatching.